Pengaruh Iklan Teleshopping Antv Terhadap Preferensi Belanja Masyarakat Kecamatan Gubeng Surabaya Masa Pandemi - Nictania Putti Andini (LPPM Stikosa-AWS, 2023)
This study aims to determine the impact of advertising messages. Home Shopping on ANTV about Community Purchasing Preferences in Gubeng District, Surabaya during a pandemic. The theory used is AIDDA & S.O.R (Stimulus, Agency, Response). The method used in this study is a quantitative method, using a questionnaire to draw conclusions from the data. The sampling technique used in this study used a sample quota. Based on the research that has been done, researchers are very interesting concluded that there was a significant effect of teleshopping advertisements on ANTV on people's purchasing preferences in Gubeng District, Surabaya during the pandemic. The correlation coefficient is 0.694 with an influence trend of 64.4%. Communicators can receive and process advertising message stimuli so that there is a change in attitude, namely the interest in making transactions by 64.4%.